2007
DOI: 10.1088/0953-8984/19/47/476202
|View full text |Cite
|
Sign up to set email alerts
|

Density of states in Bi12TiO20from time-of-flight measurements

Abstract: Two sillenite crystals of Bi12TiO20, one intrinsic and one lead doped, have been studied by means of the time-of-flight (TOF) experiment. After a short presentation of the technique, we return to the different methods proposed to extract the transit time from the current transients recorded with the TOF experiment. Further, we illustrate the possibility of extracting the density of states from these transients by means of a Laplace transform applied to the variation with time of the transient currents. Then we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Comparatively, the conduction band (CB) position of BTO was more negative, and the valence band (VB) position of BO was more positive. Hence, according to the fact that pure BTO and BO both were p-type conductivity, it can be concluded that the produced BBTO composite was an interleaved type II and p–p heterojunction. ,, Such energy band arrangement favored the separation of carriers in BBTO and promoted the photocatalytic efficiency. , …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Comparatively, the conduction band (CB) position of BTO was more negative, and the valence band (VB) position of BO was more positive. Hence, according to the fact that pure BTO and BO both were p-type conductivity, it can be concluded that the produced BBTO composite was an interleaved type II and p–p heterojunction. ,, Such energy band arrangement favored the separation of carriers in BBTO and promoted the photocatalytic efficiency. , …”
Section: Resultsmentioning
confidence: 96%
“…It is known that the stability and reusability of a photocatalyst have been the focus for their applications. , Figure d shows the RhB photodegradation by the BBTO photocatalyst after six cycles with visible light irradiation, where its photocatalytic activity was largely maintained after six successive runs.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we also want to underline that the peak indicated by an arrow was detected from a time of flight experiment performed on the same crystal with the same wavelength as we used for the TPC [7].…”
Section: The Bto:pb Density Of Statesmentioning
confidence: 99%